Geranyl acetate synthesis in a packed-bed reactor catalyzed by novozym in supercritical carbon dioxide and in supercritical ethane - Couto, Ricardo (2011)
The esterification reaction of geraniol with acetic acid (100 mM/100 mM) catalyzed by immobilized Candida antarctica lipase B (Novozym 435) was studied in supercritical carbon dioxide (sc-CO2) and in sc-ethane in a packed-bed reactor(PBR). In sc-CO2 it was easy to adjust the water activity (aw) in the reaction mixture to levels leading to good enzyme performance. Enzyme stability was high and steady-state conversions could be achieved that exceeded the largest conversions measured in batch stirred-tank reactors (BSTRs), which is probably due to the lower aw levels achieved in the PBR. In sc-ethane, where the solubility of water is lower, high steady-state conversions could be attained only by preventing the accumulation on the enzyme bed of the water produced during reaction. The kinetic parameters for the reaction in sc-CO2 were determined using previously published data obtained in a BSTR, and a model was developed for the PBR that included those kinetic parameters. This model was able to predict with reasonable accuracy the behavior of the PBR. Slight differences were observed for some operating regions, probably due to the influence of aw in the activity of the enzyme, which is not included in the model.